Aerobic, anaerobic, and skill performance with regard to classification in wheelchair rugby athletes - Morgulec-Adamowicz, N.; Kosmol, A.; Molik, B.; Yilla, A. B.; Laskin, J. J. (Research Quarterly for Exercise and Sport, 2011)
The purpose of the study was to examine the sport-specific performance of wheelchair rugby players with regard to their classification. A group of 30 male athletes from the Polish Wheelchair Rugby League participated in the study. The seven International Wheelchair Rugby Federation classes were collapsed into four groups. Standardized measures of aerobic, anaerobic, and skill performance were examined to identify performance differences among the four groups. Major findings were that most differences were between Group I players and all others and that anaerobic performance was the most sensitive to classification differences. Another important finding was that for all other groups, with one exception, adjacent groups did not differ in anaerobic, aerobic, and sport-specific skill performance. The results of this study demonstrate the need to investigate other performance measures that will help in evaluating the current wheelchair rugby classification system.